Retorika Islam Nusantara Elit Intelektual NU di Media Online - Safitri, Dini (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2017)
This article reports on study of NU’s elite intellectual rhetoric on Islam Nusantara published by NU’s official web portal. Using Stephen Toulmin's rhetorical analysis and the Teun A. van Dijk's text analysis, the findings illustrate that the rhetoric of NU's elite intellectuals on Islam Nusantara, conveyed through their articles, frequently presents the background attributed to the NU's 33rd summit and provides argumentation based on a local situation that are directed to make the conclusion that Islam Nusantara is a distinctive Islam of NU. It is not aimed to localize Islam, but it attempts to understand and perform Islamic teachings, without putting aside the place where Muslims are held and embraced.